2021
DOI: 10.1038/s41598-021-88657-y
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the potential of a native natural biosorbent for the elimination of an anionic textile dye Cibacron Blue in aqueous solution

Abstract: This work is devoted to the adsorption of Cibacron Blue (CB) an anionic textile dye, on bean peel (BP) an agricultural waste with neither activation nor carbonization. The adsorption was realized in batch configuration at ambient temperature in acidic medium. The adsorbent was characterized by FTIR, SEM and BET analyses; the equilibrium isotherms and kinetics were also studied. It has been found that this waste could be used as a low-cost biosorbent for CB elimination under optimal working conditions. The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…In type H2, this wide loop has a heterogeneous pore structure with sizes ranging from 2-6 nm and more than 10 nm in size. Thus, adsorption-desorption di erences occur because they have heterogeneous sizes due to the blockage of smaller pores with a pore shape like a pile of paper with looser gaps (Grabi et al, 2021). The BET analysis data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In type H2, this wide loop has a heterogeneous pore structure with sizes ranging from 2-6 nm and more than 10 nm in size. Thus, adsorption-desorption di erences occur because they have heterogeneous sizes due to the blockage of smaller pores with a pore shape like a pile of paper with looser gaps (Grabi et al, 2021). The BET analysis data are presented in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 14 shows that there is a wavelength shift that is carried out by adsorption which will detect the functional group of the compound. the dye adsorption process is in uenced by the number of functional groups, types of functional groups, interaction processes, adsorbent chemistry (Grabi et al, 2021). The results of the FT-IR spectrum can be seen in Figure 14 showing the appearance of a peak at the wavenumber of 2854 cm −1 because it has been in contact with the adsorbate.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the biosorption capacity is inversely proportional to biosorbent dose. Therefore, its increase leads to a direct decrease in adsorption capacity due to the unsaturation of the adsorption sites [47][48].…”
Section: Biosorbent Dose Effectmentioning
confidence: 99%
“…However, studies have also shown that some biomasses can be used as biosorbents without pre-treatment, and these are known as natural biosorbents. Numerous biomass materials such bean peel [13], banana and orange peel [14], sunflower stem pith [15], weeds [16], Carica papaya wood [17], corn straw [18], tea waste [19], pine tree leaves [7], cashew nutshell [20], and pineapple leaf powder [21] have been used as natural biosorbents to remove dyes from wastewater. Limited studies have also explored the potential of using untreated seaweeds as a natural biosorbent for dye removal [22,23].…”
Section: Introductionmentioning
confidence: 99%